Murder in passy [large type] - Black, Cara, 1951- (Black, Cara, 1951- Aimée Leduc investigation., 2011)
The village-like neighborhood of Passy, home to many of Paris's wealthiest residents, is the last place one would expect a murder. But when Aimée Leduc's godfather, Morbier, a police commissaire, asks her to check on his girlfriend at her home there, that's exactly what Aimée finds. Xavierre, a haut bourgeois matron of Basque origin, is strangled in her garden while Aimée waits inside, and Morbier is the prime suspect.